The Limitations of Diazepam as a Treatment for Nerve Agent–Induced Seizures and Neuropathology in Rats: Comparison with UBP302 - Apland, James P. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Exposure to nerve agents induces prolonged status epilepticus (SE), causing brain damage or death. Diazepam (DZP) is the current US Food and Drug Administration–approved drug for the cessation of nerve agent–induced SE. Here, we compared the efficacy of DZP with that of UBP302 [(S)-3-(2-carboxybenzyl)willardiine; an antagonist of the kainate receptors that contain the GluK1 subunit] against seizures, neuropathology, and behavioral deficits induced by soman in rats. DZP, administered 1 hour or 2 hours postexposure, terminated the SE, but seizures returned; thus, the total duration of SE within 24 hours after soman exposure was similar to (DZP at 1 hour) or longer than (DZP at 2 hours) that in the soman-exposed rats that did not receive the anticonvulsant. Compared with DZP, UBP302 stopped SE with a slower time course, but dramatically reduced the total duration of SE within 24 hours. Neuropathology and behavior were assessed in the groups that received anticonvulsant treatment 1 hour after exposure. UBP302, but not DZP, reduced neuronal degeneration in a number of brain regions, as well as neuronal loss in the basolateral amygdala and the CA1 hippocampal area, and prevented interneuronal loss in the basolateral amygdala. Anxiety-like behavior was assessed in the open field and by the acoustic startle response 30 days after soman exposure. The results showed that anxiety-like behavior was increased in the DZP-treated group and in the group that did not receive anticonvulsant treatment, but not in the UBP302-treated group. The results argue against the use of DZP for the treatment of nerve agent–induced seizures and brain damage and suggest that targeting GluK1-containing receptors is a more effective approach.